Modernidad y modernización en América Latina: una aventura inacabada - Morales Martín, Juan Jesús; Marín Bravo, Álvaro (Nómadas. Critical Journal of Social and Juridical Science, 2010)
In the sociological literature we find diverse ways of approaching the Latin-American experience with the modernity. All these approximations answer to processes and unequal, dispersed phenomena in the time and in the space. The convulsion of the orders and of the social institutions from beginning of the 20th century, accentuated after the Second World war, has produced an increasing penetration of meanings of the modernity in the social fabric of Latin America. In this respect, the offer of this article is to realize a genealogy of the genesis and metamorphosis of the project of the modernity in Latin America. The discussion presents it will lead us to failing, to break or simply to respect some limits established on the possibility of the modernity in the region and, especially, to try to understand the specific way that has Latin America of being in the modernity. For it, we will try to understand in sociological key the “Latin American modernity” as a historical process full of determinants and cultural, economic, political and social shades. This will make us favour the approach of “multiple modernity” that opens the possibility of thinking about “another modernity” for the region. The aim is to consider the aspects of the Latin American modernity and, principally, to face its lacks, its faults and its lagoons, attending to the contradictions that have guided the project of the modernity in Latin America for a particular way, that the difference of the rest of the western societies.
Keywords: Modernity; Modernization; Latin America; Multiple modernity; Identity